VD_FINDINFO HC / 2009 / 310 vom 20. August 2009 - VD Tribunal cantonal (2009)
CONTRAT DE TRAVAIL, DÉLAI DE RÉSILIATION, LIBERTÉ CONTRACTUELLE, CONTRAT DE DURÉE INDÉTERMINÉE | 335 al. 1 CO, 335c al. 1 CO, 335c al. 2 CO, 452 al. 1ter CPC, 452 al. 2 CPC, 46 al. 1 LJT, 46 al. 2 LJT